PEMODELAN PENJALARAN GELOMBANG TSUNAMI DAN ANALISIS DAERAH JANGKAUAN DI NAGARI MANGGOPOH PALAK GADANG ULAKAN - Fudla, Mariratul; Prarikeslan, Widya (JURNAL BUANA, 2024)
Abstract The problem in Nagari Manggopoh Palak Gadang Ulakan is that there is no map and modeling analysis of the propagation and coverage area of tsunami waves with the 2023 earthquake scenario in Nagari Manggopoh Palak Gadang Ulakan. With the research aim of analyzing the form of modeling of the propagation and coverage area of tsunami waves with the 2023 earthquake scenario in Nagari Manggopoh Palak Gadang Ulakan. The method used in research is quantitative with a systematic investigation of a phenomenon by collecting data that can be measured using statistical, mathematical or computational techniques. Modeling the propagation of tsunami waves in Nagari Manggopoh Palak Gadang Ulakan using scenario 1 with Mw 8.9 located at coordinates 99.81 E-0.87 South Latitude which results in tsunami wave propagation reaching 7.5 meters and scenario 2 with Mw 8.9 located at coordinates 97, 95 BT-1.44 South Latitude resulted in a tsunami wave propagating up to 4.5 meters.